Mobile Learning Research Trends in Indonesia: A Systematic Literature Review - Ichwan Restu Nugroho; Insih Wilujeng; Zuhdan Kun Prasetyo (Jurnal Penelitian Pendidikan IPA, 2023)
The existence of mobile devices and advances in technology has made mobile learning one of the learning trends in schools ranging from elementary to high school and even college in Indonesia. This content analysis research aims to systematically analyze trends in the development of mobile learning in Indonesia based on analysis of articles found in international and national journals. Based on the search results obtained 61 articles. Article analysis uses the Paper Classification Form (PCF) instrument which has been tested for validity and reliability. Based on the results of the analysis, the most widely used research method for mobile learning is Quasi-Experiment (44%) by testing the results of Research and Development (82%) of mobile learning products. Most mobile learning is for high school students (57%). Android Mobile Learning Apps (52%) are the most widely used mobile learning products in research. Learning outcomes (19%) are the most dominant bond variables related to mobile learning. This result can be used as a reference for research on the development of mobile learning media using the Android platform in science learning in schools.